Letteratura disegnata? - Barberis, Lorenzo; D’Angelo, Marco; Rastelli, Simone (Neuróptica, 2021)
Reseña de: BARBIERI, D., Letteratura a fumetti? Le impreviste avventure del racconto, Roma, ComicOut, 2019.